(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Ashawagandha is herb used for various kinds of disease especially as a nervine tonic. Considering these facts many scientific studies were carried out and its memory, anti-stress activities were studied in detail. Aims and Objectives: To study the Phytochemical analysis and Pharmacological Study of Ashwagandha (Withania somnifera) varieties and Withania somnifera (L.) Dunal wild purified with milk steam (WSWM) root powder. To study the efficacy of Wild and Cultivated varieties of Ashwagandha on rats through Elevated Plus Maze test and Morris Water Maze (MWM) model. Materials and Methods: The formulations Withania somnifera (L.) Dunal wild (WSW) root powder, Withania somnifera (L.) Dunal Nagori (WSN) root powder, Withania somnifera (L.) Dunal wild purified with milk steam (WSWM) root powder, PG (Wheat powder placebo) were subjected to preliminary phytochemical screening for the detection of various chemical constituents present. Animal experimentation was done on Wistar Albino Rats obtained from the animal house attached and are divided into three groups consisting of 6 rats per group. Nootropic agents are effectively screened using this paradigm in scopolamine-induced dementia. Elevated Plus Maze and Morris Water Maze (MWM) model are based on this phenomenon. Results: By performing phytochemical analysis, Withania somnifera (L.) Dunal Nagori (WSN) showed the presence of alkaloids, carbohydrates, glycosides, phytosterols, saponins, proteins and amino acids. Withania somnifera (L.) Dunal wild purified with milk steam (WSWM) showed the presence of alkaloids, carbohydrates, glycosides, proteins and amino acids and wheat powder placebo (PG) showed the presence of alkaloids, carbohydrates, glycosides, saponins, phenolic compounds, tannins, proteins amino acids and flavonoids. Conclusion: The formulation group 3 (WSWM) showed remarkable reduction in the transfer latency time (in elevated plus maze test) from the acquisition day to the retention day and therefore considered Group 3 is statistically significant. The formulation group 3 (WSWM) showed remarkable reduction in the latency scores in Morris water maze and hence Group 3 (Ashwagandha wild purified with milk steam (WSWM) root powder) is statistically significant.